Saving the World: A Brief History of Communication for Development and Social Change By: Emilie McAnany (2012) Urbana, IL: University of Illinois Press 181 pages, including index and reference lists $27.00 paperback - Drew F. Slattery (Journal of International Agricultural and Extension Education, 2017)
Emile McAnany published his text Saving the World: A Brief History of Communication for Development and Social Change as part of a University of Illinois commissioned multi-volume series on the history of communication and communication studies in 2012. McAnany uses his more than 50 years of scholarly communication research and international development practice to trace the history of Communication for Development (C4D) from its inception post World War II (WWII) with the Marshall plan to the current time, through four major paradigms. Put simply, this book illustrates the use of communication by development practitioners as it has evolved over time, culminating in a series of recommendations by the author based on the lessons learned associated with this history.